Coke's water bomb - Turner, Libby (Australia : BBC, 2004)
On a British sitcom, two characters bottled tap water and sold it as Peckham Spring Water. More recently, Coca-Cola launched its purified-water lifestyle drink, Dasani, in the U.K. The connection was not overlooked. This program tracks Dasani's progressive PR nightmare in Britain -- first as newspapers screamed'Coke Sells Tap Water for 95p,' and then as Coca-Cola recalled 500,000 bottles due to potentially carcinogenic contamination at their factory. It also considers an even larger problem as worldwide Coke sales continue to flatten: without Dasani, the soft drink giant has no bottled water product for the lucrative European market
Title from title screen
Series producer, Mark Gregory ; series editor, Clive Edwards
Narrator, Rajan Datar
DVD format
Keywords: Coca-Cola Company; Soft drink industry; Bottled water industry; Bottled water -- Marketing; Advertising -- Bottled water